Effect of Storage Conditions, Packaging Material and Storage Period on Seed Germination and Seed Viability of Gazania splendens L. - K.K. DHATT; RAMESH KUMAR (Seed Research, 2026)
The investigations were carried out with the objective to find the optimum storage conditions for Gazania seeds to increase the germination and viability of Gazania seed. The highest germination (47.94%) and viability (63.29%) was recorded in cold store after 18 months than ambient storage and incubator. Among the packaging, seed kept in desiccator gave the maximum germination (43.23%), followed by aluminium foil (41.36%) irrespective of storage temperature. The seed maintained above 92 per cent germination during the initial three months but significant decline was observed in the proceeding months, being 80.67 per cent after six months, 29.51 per cent after nine months. The cold storage resulted in the maximum seed germination (48.33%) in succeeding harvesting season (April) after nine months of storage when packed in aluminium foil. Similarly, the seeds stored in desiccator under cold store recorded the maximum viability (52.25%) after 18 months of storage. The polyethylene bag gave the maximum viability (75.67%) after nine months in April that was equivalent to desiccator and aluminium foil kept in cold store (74.67%). The highest viability was obtained in desiccator (53.67%) in cold store in next planting season viz., September.